Pyrethroid genetic resistance in the dengue vector (Aedes aegypti) in Posadas, Argentina - Fay, Jessica V.; Espinola, Sonia L.; Boaglio, María V.; Blariza, María J.; Lopez, Karen; Zelaya, Fabian; Kulkarni, Manisha A.; Argüelles, Carina F.; Ferreras, Julian A.; Miretti, Marcos M. (Frontiers in Public Health, 2023)
Pyrethroids are extensively used to control adult populations of the arboviral vector Aedes aegypti, raising concerns regarding the increasing frequency and distribution of insecticide resistance mutations (kdr: knock-down resistance) in the voltage-gated sodium channel gene (Nav). The widespread use of pyrethroids imposes a threat to the success of mosquito control and the environment. In this study, we investigated the presence of two kdr mutations (V1016I and F1534C) in the Nav gene and their distribution across four neighborhoods in Posadas, Argentina, with different Ae. aegypti abundance and contrasting socioeconomic status (SES). Alleles at each locus were interrogated using TaqMan SNP genotyping assays in DNA extracted from adult females collected in a longitudinal study. We report the presence of both pyrethroid resistance alleles (kdr 1016I = 29.08%; kdr 1534C = 70.70%) among adult females. The frequency of combined kdr genotypes reveals that approximately 70% of local adult females have enhanced resistance to pyrethroids. Both, the proportion of resistant adult females (with at least one kdr allele in each locus) and Ae. aegypti abundance showed an uneven distribution between neighborhoods with different SES (p < 0.001). In high-SES neighborhoods, we found more mosquitoes and a higher frequency of pyrethroid resistance, possibly as a consequence of different public health interventions, social habits, and insecticide use. This is the first report of kdr mutations in Ae. Aegypti in the northeast region of Argentina. Our results focus on the need for within-population (city) distribution analyses of kdr mutations and highlight the relevance of incorporating insecticide resistance monitoring within the Integrated Vector Management initiative.